Protective effects of different doses of inhaled fenoterol on methacholine-induced bronchoconstriction in asthmatic children - Gomez, Irma Douglas [UNIFESP] (1998)
OBJECTIVE: To evaluate the protective effect of different doses of inhaled fenoterol (F) on bronchoconstriction induced by methacholine (M).DESIGN: randomized double-blind study.SETTING: Referrence center.PARTICIPANTS: 9 children (aged from 7 to 15 years old), with mild or moderate asthma and allergic to D. pteronyssinus.INTERVENTION: On the first day, the M concentration necessary to induce a 20% fall in the forced expiratory volume in the first second (FEV1; PC20FEV1) was determined using closed circuit inhalation (De Vilbiss 646). On subsequent days, the children inhaled a dose of F (25 or 50 or 100 or 200 µg) through the same circuit and, after 15 minutes the FEV1 was measured, becoming the basal value. Bronchoprovocation was then initiated using the concentration prior to the PC20FEV1 of the first day and continuing until there was a 20% fall in the FEV1. This concentration was the new PC20FEV1.RESULTS: F in a dose of 25 µg protected 2 of the 9 children, in a dose of 50 mg protected 4 of the 9 and in doses of 100 and 200 µg protected all children. We did not observe any relationship between the magnitude of the bronchodilation and bronchoprotection induced by the inhalation of F. CONCLUSIONS: Our results suggest that a dose of 100 µg of F is capable of inducing bronchoprotection in children with mild/moderate asthma.